Karakter Religius Siswa dan Pengaruhnya Terhadap Sikap Disiplin di Sekolah Menengah Pertama - Jalwis Jalwis (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Character education is present as a solution for the degradation of morals and morality where character education is designed by educators with the aim of forming characters who have good character and behavior. The purpose of this study was to determine the religious character of students and discipline as well as the impact of character on student discipline attitudes at the State Primary School 2 Sungai Penuh. This type of research uses qualitative research and data collection techniques, namely observation, documentation, and interviews. The results of this study are that the formation of student discipline through religious activities at SMP N 4 Sungai Penuh is carried out by religious teachers, namely through worship practices such as prayer, ablution, the practice of memorizing short verses and reading prayers. While the impact of religious attitudes on students' discipline in SMP N 4 Sungai Penuh that the visible impact of students is the religious character of students through the practice of worship in religious subjects can be seen from changes in students' attitudes and behavior.